Sea urchin Paracentrotus lividus (Lamark 1816) eggs and endotrophic larvae:potential of their use as marine larval fish first-feeding - Gago, João André Evaristo de Matos, 1974- (2010)
Tese de doutoramento, Biologia (Biologia Marinha), 2010, Universidade de Lisboa, Faculdade de Ciências